Here on the island : being an account of a way of life several miles off the Maine coast - Pratt, Charles, 1926-1976; Van Doren, Harold S. (New York : Harper and Row, 1974)
A professional photographer illustates his own account of year-round life on an island several miles off the coast of Maine
Keywords: Islands -- Maine; Maine -- Description and travel; Maine -- Social life and customs